Spatial-heterogeneous granulation of organic amendments and chemical fertilizer stimulated N2O emissions from agricultural soil: An microcosm study. (1st January 2021) - Yang, Xinyi; Duan, Pengpeng; Li, Guitong; Zhao, Xiaorong; Lin, Qimei; Zhu, Kun
Abstract: The promising application modes of organic fertilizer (OF) and chemical nitrogen (N) fertilizer (CF) could be the homogeneous granulation (HG: OF and CF are distributed spatially evenly) and spatial heterogeneous granulation (SG: OF and CF are distributed separately in space), where the N transformation processes, such as the nitrous oxide (N2 O) emissions, are greatly influenced by the spatial distribution of the OF and CF, particularly. Currently, there is a lack of in-depth understanding about the microbial mechanisms of the SG and HG application on N2 O emissions, and the related functional guilds (ammonia oxidizers and heterotrophic denitrifiers) respond to the granular fertilizer is yet not known. In the present study, we made CF ( 15 N-(NH4 )2 SO4 ), cow compost and maize straw (2% or 8% based on the N proportion) into granular of 1 cm in diameter, in HG and SG forms, respectively, and then applied these granules in soils for 80 days incubation. Results showed that, compared with HG treatments, the SG treatment promoted the ammonium (NH4 + ), nitrate (NO3 − ) and microbial biomass carbon (MBC) intensities, and increased the N2 O emissions possibly through ammonia oxidize bacteria dependent nitrification and fungal denitrification. In addition, the high maize residues proportion in organic fertilizer significantly mitigated N2 O emissions by the coupled impacts of suppressed nitrification and enhanced denitrification enzyme activity with high C input. Overall, our results suggest that spatial heterogeneous granulation of and CF may induce higher risk of N2 O emissions and the higher proportion of maize residues could potentially mitigate such increased emissions. Highlights: Spatial heterogeneous granulation increased the N2 O emissions. High maize residues proportion in organic fertilizer decreased N2 O emissions. AOB act as the N2 O source, whereas nosZ Ⅱ act as the N2 O sink.